Evaluation of selenium bioavailability to Brassica juncea in representative Chinese soils based on diffusive gradients in thin-films (DGT) and chemical extraction methods. Issue 9 (28th July 2020) - Zhang, Zengyu; Shen, Fangke; Gu, Minghua; Liu, Yongxian; Pan, Liushu; Shohag, M. J. I.; Li, Tingting; Wei, Yanyan
Abstract: Selenium (Se) is an essential micronutrient for humans but is toxic when consumed in excess through the food chain, such as vegetables. Therefore, it is imperative to understand the relationship between the bioavailability of Se in soil and its uptake in edible parts of vegetables. This study investigated Se bioavailability of Brassica juncea in six representative Chinese soils treated with different concentrations of exogenous selenate fertilizer (0–2 mg·kg −1 ) by comparing diffusive gradients in thin-films (DGT) and chemical extraction methods. The correlation coefficients between the Se uptake by Brassica juncea and soil available Se determined by different extraction methods was as follows: DGT > KCl > Water > EDTA > KH2 PO4 > NaHCO3 extractions. In addition, soil properties were correlated between Brassica juncea and soil Se concentrations determined by chemical extraction methods, while the DGT method was independent of soil properties. DGT was more suitable for the measurement of Se thresholds for Udic Ferrisols, Mollisols, Stagnic Anthrosols, Fluviogenic Loamy Paddy soil, Silty Loam soil, and Calcaric Regosols with values of 373.34, 648.68, 436.29, 589.84, 295.35, and 464.95 μg·L −1, respectively. Thus, DGT may be an effective method for the prediction and evaluation of Se bioavailability to Brassica juncea in different soil types.